Mona Lisa in Camelot : how Jacqueline Kennedy and Da Vinci's masterpiece charmed and captivated a nation /: how Jacqueline Kennedy and Da Vinci's masterpiece charmed and captivated a nation. (©2008) - Unknown
No abstract available